2001
DOI: 10.1002/hup.326
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine levels in saliva: associations with psychosocial factors and behavioural effects

Abstract: The present study had two main aims. The first was to examine associations between psychosocial factors, health-related behaviours, regular level of caffeine consumption, time of day and levels of caffeine in saliva following acute caffeine challenges. The second aim was to determine whether individual differences in changes in performance following ingestion of caffeine were related to levels of caffeine in saliva. One hundred and forty-four young adults participated in the study. Questionnaires were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
(13 reference statements)
1
11
1
Order By: Relevance
“…However, Brice and Smith [25,26] found that the improved mood and enhanced performance after a single dose of 200 mg were also present with four doses of 65 mg given at hourly intervals.…”
Section: General Psychotropic Effects Of Caffeinementioning
confidence: 99%
“…However, Brice and Smith [25,26] found that the improved mood and enhanced performance after a single dose of 200 mg were also present with four doses of 65 mg given at hourly intervals.…”
Section: General Psychotropic Effects Of Caffeinementioning
confidence: 99%
“…The mean age of the sample was 20.96 years (range 19-23 years); the mean weight was 71.91 kg (range 60-86 kg); and the mean daily caffeine consumption, assessed by self-report, 210 mg (range 100-375 mg). In order to directly compare the two methods of administering the caffeine conditions, it was essential to control for factors known to influence caffeine metabolism (Brice and Smith 2001b). Participants were not eligible for the study if they were female, taking medication or if they smoked.…”
Section: Participantsmentioning
confidence: 99%
“…It was predicted on the basis of our previous research, and the findings of other researchers, that caffeine would increase alertness (Smith et al 1993;Warburton 1995;Brice and Smith 2001a), increase anxiety (Loke 1988;, reduce simple reaction time (Clubley et al 1979;Smith et al 1994;Smith et al 1997) and improve sustained attention (Smith et al 1992;Brice and Smith 2001b), dual-task performance (Kerr et al 1991) and the encoding of new information (Smith AP et al 1999). The aim of the present study was to determine whether these effects would be observed with both administration of multiple small doses and a single large dose of caffeine.…”
Section: Introductionmentioning
confidence: 96%
“…Among documented clinical effects of caffeine are increased heart rate, systolic blood pressure and left ventricular output [7,8,11] stimulation of autonomic responses [12,13] decreased tone of the gastrointestinal smooth muscles increased ocular pressure in glaucoma patients [14] central nervous system excitation and increased alertness [2,5,9] However, the only study we were able to find documenting the response of salivation to ingestion of any methylxanthine was a retrospective analysis of Pavlovian date [15]. Nevertheless, in the dental community, the belief that caffeine consumption decreases salivary production is widely held [6].…”
Section: Discussionmentioning
confidence: 99%
“…Like all exocrine secretions, salivary production is under the control of the autonomic nervous system, but physical factors such as hypovolemia and dehydration can also play a role. Thus, various systemic conditions, medications, and psychological factors can affect salivary output [1,2].…”
Section: Introductionmentioning
confidence: 99%